PRINCIPLES OF TREATMENT IN BALAROGA-AN AYURVEDA PURVIEW - Gawali, *Komal; K.Vyas, Mahesh; Vyas, Hitesh A. (International Journal of Ayurveda and Pharma Research, 2016)
Ayurveda has emphasized on the quality of life along with its longevity. The Acharyas have categorized the stages of life into various forms. Balyaavastha (childhood) is one such phase of life that differs in the Ahara (diet), Vihara (lifestyle) and Aushadhi (medicines) than the other phases. The treatment modalities also differ in this phase. The synonyms of Bheshaja (medicine) have been defined by Acharya Charaka as Chikitsitam (treatment), Vyadhiharam (disease removal), Pathyam (wholesome agents) Sadhanam (modes of treatment), Aushadham (drugs), Prayashchitam (corrective measures), Prashamanam (alleviation), Prakritisthapanam (restoration) and Hitam (beneficial). Each term has its own that defines every aspect of treatment. The underlying theme of treatment in Balaroga can be understood by the proper understanding of the implications of the term Bheshaja. The variations of treatment according to the various stages of the diseases can be understood by these terms. This paper aims at discussing the principles of treatment in Balaroga from Ayurveda perspective. The treatment of various diseases of children deal with the same underlying basic principle as adults but the only difference is a slight shift of thought in it. The paper aims at highlighting the treatment principles in Balaroga. For this purpose, the literature was reviewed from the internet, and the Ayurveda classics along with their commentaries. The complexities of treatment in Balaroga are highlighted on the basis of this definition of the term Bheshaja.